ICT in the graduate profile of Latin American law schools according to the Scimago ranking - González Aguilar, Hugo (2023)
This study analyzes ICT in the graduate profile of Latin American law schools, according to the 2022 Scimago ranking. A qualitative analysis has been carried out based on the discourse or content of the profiles that have been disseminated through their Web pages. The profiles, in the field of ICT, show that this is developed as an instrumental or complementary competence, is used in a diverse way, serves as a basis for the elaboration of legal instruments and strategies, is related to other areas and allows the lawyer to interconnect with the global world of work.